Pengaruh Industri Pengolahan Terhadap Pertumbuhan Ekonomi di Jawa Timur - Muhammad Akbar Perdana; Alviolita Tri Amanda; Muhammad Yasin (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to determine how much the processing industry contributes to East Java's economic growth. This type of research uses descriptive research methods. Based on its nature, the types of data to be collected in this study are qualitative data and quantitative data. Data sources in this study include secondary data sources, namely parties who have collected and processed data from the first party. The secondary sources of this research are the Central Bureau of Statistics of Java province in the form of East Java growth data from 2012 to 2016 and the East Java Provincial Perindag Office in the form of quarterly time series data for the period 2012 to 2016. The results showed that the processing industry sector had a positive and significant effect on the economic growth of East Java Province.